Antioxidant Activity and Pancreatic Lipase Inhibition of Curcuma aeruginosa Roxb Rhizome Fractions - Suharsanti, Ririn; Wahyuono, Subagus; Yuniarti, Nunung; Astuti, Puji (Jurnal Biodjati, 2024)
Antiobesity with a lipase inhibitor mechanism will block the hydrolysis of triglycerides into fatty acids and glycerol, while antioxidant compounds are very useful in conditions of obesity to prevent excess damage from degenerative diseases. Curcuma aeruginosa Roxb extract has been proven to have the effect of inhibiting pancreatic lipase so further effects will be seen at the fraction level. The purpose of this research is to investigate the phytochemical components ,antioxidant activity and pancreatic lipase inhibition of Curcuma aeruginosa Roxb fractions. Ethanolic extract of the Curcuma aeruginosa Roxb rhizome was separated using the solid-liquid chromatography with 3 different solvents (n-hexane, ethyl acetate, ethanol) to give n-hexane (HF), ethyl acetate (EAF), and ethanol (EF), and the insoluble (IF) fractions. Each fraction detected phenolics, flavonoids, alkaloids, tannins, saponins, triterpenoids/steroids. EF has the highest total flavonoid and phenolic content. Antioxidant activity of all fractions were measured using DPPH reduction, ABTS, and FRAP methods. The best antioxidant activity of all fractions using the DPPH method was EF with IC50 21.93 ± 3.39µg/mL, ABTS method was HF with IC50 24.56±1,03 µg/mL and FRAP method was IF with IC50 20.79±1,03 µg/mL. Totals of phenolics and flavonoids in EF strongly support the antioxidant activity of the DPPH method. The highest inhibition of pancreatic lipase was found in EAF at 35.16±0.24 % (100 µg/ml). There was significant difference between EAF and xenical (orlistat) (p<0,05).